Primer structure of V belt - WANG XUEPAN; LI WENBO; XIN ZHENXIANG; PAN WANDONG; HU ENBO (2017)
The utility model relates to a primer structure of V belt, including primer and primer curtain cloth, is the primer sizing material number of piles 2 4 the layer, primer sizing material hardness from top to bottom scales up in proper order, and the primer sizing material curvature radius from top to bottom steadily decrease in proper order, is the primer curtain cloth number of piles 2 4 the layer, the primer curtain cloth width from top to bottom scale up in proper order. The utility model discloses when increasing V belt primer transverse rigidity, reduced vertical bending stress that primer hardness or primer curtain cloth result in again, reduce the energy consumption loss, improve transmission efficiency. 本实用新型涉及种三角带的底胶结构，包括底胶和底胶帘布；底胶胶料层数为2-4层，底胶胶料硬度由上至下依次递增，底胶胶料曲率半径由上至下依次递减；底胶帘布层数为2-4层，底胶帘布宽度由上至下依次递增。本实用新型在增加三角带底胶横向刚度的同时，又减小了底胶硬度或底胶帘布导致的纵向弯曲应力，降低能耗损失，提高传动效率。